1975
DOI: 10.1161/01.res.37.6.855
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine turnover in the heart and spleen of the cardiomyopathic Syrian hamster.

Abstract: Although a reduction in myocardial norepinephrine stores in cardiac hypertrophy and congestive failure is well documented, norepinephrine turnover has been inadequately studied in such hearts. We compared norepinephrine turnover in control and cardiomyopathic hamsters by following the decline in specific activity of myocardial norepinephrine after labeling with an intraperitoneal tracer dose of 3 H-norepinephrine. Adult myocardial norepinephrine concentrations were not attained until 4 weeks of age in both str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…It is well known that norepinephrine is a potent stimulus for cyclic AMP production in the heart. 36 Sole et al 37 found a considerable increase in cardiac norepinephrine turnover as early as the myolytic phase of hamster cardiomyopathy. Furthermore, Nair and co-workers 24 described a similar increase in myocardial adenyl cyclase activity.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that norepinephrine is a potent stimulus for cyclic AMP production in the heart. 36 Sole et al 37 found a considerable increase in cardiac norepinephrine turnover as early as the myolytic phase of hamster cardiomyopathy. Furthermore, Nair and co-workers 24 described a similar increase in myocardial adenyl cyclase activity.…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence that both in humans, and in animal models, heart failure is associated with depletion of cardiac norepinephrine stores and augmented generalized sympathetic activity (1)(2)(3)(4). Marked increases in rates of norepinephrine turnover have been reported in this disorder (5). Under normal conditions the rate-limiting step in the biosynthesis of norepinephrine is the hydroxylation of tyrosine, which is catalyzed by the enzyme tyrosine hydroxylase (6).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, normal amounts of DBH are synthesized and released but the enzyme is peripherally inactivated. It is of considerable interest that in cardiomyopathic hamsters with heart failure there is accumulation of dopamine in the myocardium (5). This suggests that in this animal model there may be reduced availability of DBH to catalyze the hydroxylation of dopamine to norepinephrine.…”
mentioning
confidence: 99%
“…In the 20th century, improvements in analytic techniques allowed more accurate in vitro measurements of neurotransmitters such as acetylcholine, epinephrine, and norepinephrine, which provided further understanding of the interactions and responses of the parasympathetic and sympathetic systems (2,3). The use of radiolabeled versions of these neurotransmitters later offered a means to monitor in vivo pharmacodynamics and provided the first quantitative estimates of uptake and clearance of these compounds in living tissues (4,5). Research with compounds labeled with tritium ( 3 H), 14 C, and 125 I laid the groundwork for the development of compounds labeled with g-and positron-emitting radioisotopes (6).…”
mentioning
confidence: 99%
“…Much of this research involved measurement of norepinephrine turnover, a quantitative method for estimating sympathetic nerve function that has been widely used in both animal and human subjects (6). The best validated method of measuring norepinephrine turnover involves injecting radiolabeled 3 H-norepinephrine and measuring its initial uptake and then its disappearance from the heart and other organs over several hours (5,11). Studies in animals have shown that, in a variety of physiologic and pathophysiologic situations, 3 H-norepinephrine disappearance from the heart follows first-order kinetics, which can be characterized in terms of a fractional turnover rate, k, or turnover half-time, T1 (12).…”
mentioning
confidence: 99%